Issues in linguistics. Papers in honor of Henry and Renée Kahane, University of Illinois Press, Urbana-Chicago-London, 1973; 933 pp. [Volumen colectivo]. - Ávila, Raúl (El Colegio de México, 1976)
Se reseñó el libro: Issues in linguistics. Papers in honor of Henry and Renée Kahane.